KOMITMEN PT.GMF AEROASIA TERHADAP KARYAWAN PRA-PURNABAKTI MELALUI PEMBEKALAN - Ana Rusmardiana (Sosio e-Kons, 2016)
As committed and as one form of responsibility to the employees who will reach the the pre-purnabhakti, PT GMF Aeroasia provided training for about one week. The purpose of training in general is to to provide debriefing of by introducing the life choices when someday retired. This study used descriptive qualitative approach by reviewing the measured three aspects, namely; readiness of financial, physical, mental and emotional. Respondents were employees PT.GMF Aeroasia nearing pre-purnabhakti bath 23 to 56 people (a married couple). The research showed the average of the the pre-purnabhakti tend over as business investment compared to become entrepreneurs.Keyword: Work, Pre-Purna Bhakti, Entrepreneur, Invest